Community-Based Multiple Family Groups to Prevent and Reduce Violent and Aggressive Behavior: The GREAT Families Program - Smith, Emilie Phillips (2004)
This paper describes the targeted intervention component of GREAT Schools and Families. The intervention—GREAT Families—is composed of 15 weekly multiple family group meetings (e.g., 4–6 families per group) and addresses parenting practices (discipline, monitoring), family relationship characteristics (communication, support, cohesion), parental involvement and investment in their child's schooling, parent and school relationship building, and planning for the future. High-risk youth and their families—students identified by teachers as aggressive and socially influential among their peers—were targeted for inclusion in the intervention. The paper describes the theoretical model and development of the intervention. Approaches to recruitment, engagement, staff training, and sociocultural sensitivity in work with families in predominantly poor and challenging settings are described. The data being collected throughout the program will aid in examining the theoretical and program processes that can potentially mediate and moderate effects on families. This work can inform us about necessary approaches and procedures to engage and support families in efforts to reduce individual and school grade-level violence and aggression.